2010
DOI: 10.1186/1471-2164-11-152
|View full text |Cite
|
Sign up to set email alerts
|

Genome dynamics of Bartonella grahamii in micro-populations of woodland rodents

Abstract: Background: Rodents represent a high-risk reservoir for the emergence of new human pathogens. The recent completion of the 2.3 Mb genome of Bartonella grahamii, one of the most prevalent blood-borne bacteria in wild rodents, revealed a higher abundance of genes for host-cell interaction systems than in the genomes of closely related human pathogens. The sequence variability within the global B. grahamii population was recently investigated by multi locus sequence typing, but no study on the variability of puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…To obtain unbiased and more discriminatory Bartonella genotype identification, we used six housekeeping genes, as well as the host adaptability VirB5-encoding gene, enabling a more precise overview of Bartonella strain diversity from distinct rodent species. The present work unambiguously confirmed the high diversity of Bartonella genotypes recovered from woodland rodents as demonstrated in previous studies [16], [18], [47], with 63 different Bartonella genotypes retrieved from 195 infected animals among 550 captured. These genotypes were separated into three known Bartonella species: B. taylorii , B. grahamii and B. doshiae , commonly found in Europe, and one genotype related to B. rochalimae- like isolates obtained from wood mice in Sweden and Spain [15], [48].…”
Section: Discussionsupporting
confidence: 91%
“…To obtain unbiased and more discriminatory Bartonella genotype identification, we used six housekeeping genes, as well as the host adaptability VirB5-encoding gene, enabling a more precise overview of Bartonella strain diversity from distinct rodent species. The present work unambiguously confirmed the high diversity of Bartonella genotypes recovered from woodland rodents as demonstrated in previous studies [16], [18], [47], with 63 different Bartonella genotypes retrieved from 195 infected animals among 550 captured. These genotypes were separated into three known Bartonella species: B. taylorii , B. grahamii and B. doshiae , commonly found in Europe, and one genotype related to B. rochalimae- like isolates obtained from wood mice in Sweden and Spain [15], [48].…”
Section: Discussionsupporting
confidence: 91%
“…Analyses of B. grahamii isolate genomes from just three locations within 30 km of one another showed diversification, although the strains had low sequence diversity on the whole (Berglund et al. ). Therefore, use of genome regions such as these may be informative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that Bartonella (B. henselae) uses amino acids and not sugars such as glucose as its primary carbon source, probably because amino acids are more easily accessible in the host, for example, via extracellular proteolysis (85). Analyses on the level of Bartonella strains and populations revealed that the bartonellae seem to evolve in clonal complexes that exhibit considerable genome dynamics, particularly by excision and insertion of genomic islands, loss and acquisition of plasmids, and both intraspecies and interspecies horizontal gene transfer (32,33,133,197,335).…”
Section: Evolution Of the Genus Bartonellamentioning
confidence: 99%
“…The filamentous hemagglutinins of Bartonella can be separated into two clades that were apparently acquired independently from different sources. It is notable that the fha loci are associated with integrases and phage genes and that the distribution of their occurrence is very diverse even within closely related populations, pointing toward frequent exchange via lateral gene transfer (32,34). Interestingly, B. quintana does not encode any filamentous hemagglutinins, although the closely related B. henselae harbors various copies of both passengers and transporters (34).…”
Section: Other Virulence Factorsmentioning
confidence: 99%